Exenatide infusion decreases atrial natriuretic peptide levels by reducing cardiac filling pressures in type 2 diabetes patients with decompensated congestive heart failure. Issue 1 (December 2016) - Nathanson, David; Frick, Mats; Ullman, Bengt; Nyström, Thomas
Abstract Background The vascular effects exerted by GLP-1 are mediated by several synergistic mechanisms such as involvement of nitric oxide and natriuresis. Recently, it was demonstrated that atrial natriuretic peptide (ANP) is essential for the glucagon-like peptide-1 (GLP-1)-stimulated vascular smooth muscle relaxation that mediates anti-hypertensive action in rodents. Therefore a GLP-1–ANP axis has been suggested. The aim of this study was to investigate whether this effect can be demonstrated in patients with type 2 diabetes and congestive heart failure. Methods The study was a post hoc analysis of a randomized double-blinded, placebo-controlled trial. Twenty male patients with type 2 diabetes and congestive heart failure were randomized to receive a 6-h infusion of exenatide or placebo. Cardiac filling pressures were measured by right heart catheterization, and plasma levels of ANP, N-terminal pro-brain natriuretic peptide, and exenatide were measured at baseline and at the end of the exenatide infusion. Results Exenatide infusion resulted in a significant decrease of circulating ANP levels compared with placebo, concomitant with a decrease in pulmonary capillary wedge pressure (PCWP), pulmonary artery pressure (PAP) and right arterial pressure (RAP), and increased cardiac output. There was no correlation between plasma ANP levels and exenatide levels. A negative correlation between ANP levels and PCWP, PAP, and RAP, which remained significant after adjustment for plasma exenatide levels, was demonstrated during exenatide infusion. Conclusions Exenatide infusion decreases cardiac filling pressure and ANP levels. The reduction of ANP levels was primarily because of the reduction in cardiac filling pressure, independent of exenatide levels. It seems unlikely that this was mediated via ANP. Trial registration:http://www.isrctn.org/ISRCTN47533126